THE COMMUNICATIVE LANGUAGE TEACHING IN ENGLISH TEACHER SERVICE AT MTs AL-FITHRI CIMAUNG: English - Ridwan Ramadhan Ikin (Tomorrow's Education Journal, 2024)
English communicative learning is crucial for students' development, enabling them to pronounce correctly, write, speak, interpret vocabulary, and memorize. However, some students may not pay attention to the material, leading to distractions. This research identifies the advantages and disadvantages of using communicative learning in English education. It found that teachers can modify methods based on individual student characteristics and abilities. The use of CLT improved students' grades and experiences, while also fostering interest and individual guidance. Overall, effective communication learning is essential for student success. Keywords: communicative, communicative language teaching (CLT).